Temptation of the word : the novels of Mario Vargas Llosa - Kristal, Efraín, 1959- (Vanderbilt University Press, 1998)
Temptation of the Word is an ambitious and careful reading of the creative process - the origin of themes and the development of literary techniques - that Mario Vargas Llosa has brought to each of his novels, published through 1997. To understand the novelist's intellectual environment, Kristal analyzes the entire corpus of Vargas Llosa's writings (including his many books of essays and his plays), his literary influences in several languages, his intellectual biography, and his polemical activism in contentious times, all in the light of the evolution of his political views and concept of literature.